ANALISIS ASUHAN KEPERAWATAN DENGAN TEKNIK RELAKSASI AUTOGENIK UNTUK MENGATASI KECEMASAN PADA IBU PRIMIPARA - Desiana Rachmawati (2022)
Handling of anxiety that occurs in primiparous mothers can be done with pharmacological and non-pharmacological approaches. So far, more anxiety management uses pharmacological for patients with severe anxiety to the panic stage or who have maternal mental health problems such as baby blues and postpartum depression. Mild to moderate anxiety can be minimized with autogenic relaxation techniques. Autogenic relaxation technique is a relaxation technique that is in rhythm between self-control and positive suggestion that gives a calming effect on the soul. This intervention was carried out 3 times a week with a duration of 15-20 minutes. The aim is to analyze nursing care with autogenic relaxation intervention to overcome the anxiety of primiparous mothers in the hospital. Jakarta Police. This case study involved the intervention and control groups, one of which received nursing care and autogenic relaxation intervention as the intervention group and the control group only received nursing care during treatment without EBN intervention. The scale for measuring the level of anxiety specifically for primiparous mothers in the midst of the Covid-19 pandemic using PSAS-RSF-C was developed by Fallon et al., (2021) which was given to both respondents on the first and last day of treatment. Analysis of nursing care with autogenic relaxation intervention obtained significant results in reducing the anxiety level of primiparas by 6 points compared to respondents who did not receive EBN intervention. It is hoped that this case study can provide information for health services regarding the provision of non-pharmacological interventions, namely autogenic relaxation to overcome anxiety in primiparous mothers. Hopefully this research can be used as a reference for knowledge and the basis for further researchers. Especially in exploring the theory of maternal mental health and the application of evidence based nursing with autogenic relaxation to overcome anxiety in primiparous mothers.